Axial behaviour of slender concrete-filled steel tube square columns strengthened with square concrete-filled steel tube jackets. Issue 6 (April 2020) - Zhu, Tao; Liang, Hongjun; Lu, Yiyan; Li, Weijie; Zhang, Hong
This article investigates the behaviour of slender concrete-filled steel tube square columns strengthened by concrete-filled steel tube jacketing. The columns were realised by placing a square outer steel tube around the original slender concrete-filled steel tube column and pouring strengthening concrete into the gap between the inner and outer steel tubes. Three concrete-filled steel tube square columns and seven retrofitted columns ranging from 1200 to 2000 mm were tested to failure under axial compression. The experimental parameters included three length-to-width ( L / B 1 ) ratios, three width-to-thickness ( B 1 / t 1 ) ratios and three strengths of concrete jacket (C50-grade, C60-grade and C70-grade). Experimentally, the retrofitted columns failed in a similar manner to traditional slender concrete-filled steel tube columns. After strengthening, the retrofitted columns benefitted greatly from the component materials, with their load-bearing capacity and ductility notably enhanced. These enhancements were mainly brought about by sectional enlargement and good confinement of concrete. A finite element model was developed using ABAQUS to better understand the axial behaviour of the retrofitted specimens. A parametric study was conducted, with parameters including the length of the column, thickness of the outer steel tube, strength of the concrete jacket, yield strength of the outer steel tube, thickness of the inner steel tube and strength of the inner concrete. Furthermore, the finite element model was adopted to study the behaviour of rust-damaged and post-fire slender concrete-filled steel tube square columns strengthened by square concrete-filled steel tube jacketing. A modified formula was proposed to predict the load-bearing capacity of retrofitted specimens, and the numerical results agreed well with the experiments and the finite element results of undamaged, rust-damaged and post-fire specimens. It could be used as a reference for practical application.